Through the eyes of a whistle-blower : how Sherry Hunt spoke up about Citibank's mortgage fraud - Waytz, Adam; Kilibarda, Vasilia ([London] : SAGE, 2016)
In 2011, Sherry Hunt was a vice president and chief underwriter at CitiMortgage headquarters in the United States. For years she had been witnessing fraud, as the company bought billions of dollars in mortgage loans from external lenders that did not meet Citi credit policy and sold them to government-sponsored enterprises (GSEs). This resulted in Citi selling to GSEs such as Fannie Mae and Freddie Mac pools of loans that were considerably defective and thus likely to default. This study explains how - and why - Sherry Hunt exposed Citibank's fraudulent activities.
Originally Published in: Waytz, A., & Kilibarda, V. (2014). Through the Eyes of a Whistle-Blower: How Sherry Hunt Spoke Up About Citibank's Mortgage Fraud. 5-214-256. Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on online resource; title from home page (viewed on May 3, 2016).
Keywords: elektronické knihy; electronic books; Citibank (New York, N.Y.); Business ethics -- Case studies; Whistle blowing -- Case studies; White collar crimes -- Case studies